Intestinal microbiota-mediated dietary fiber bioavailability - Guo, Kangxiao; Yao, Zihan; Yang, Tao (Frontiers in Nutrition, 2022)
Dietary fiber is a kind of carbohydrate that cannot be digested and absorbed by the small intestine of humans but can be fermented in all or part of the large intestine and is significantly healthy for the human body. With the improvement in living standards, people pay more attention to their intestinal health, and the relationship between dietary fiber, intestinal microecological and body physiological balances, and their molecular connection mechanism has become a research hot spot. In this study, we reviewed its mediated bioavailability to provide a basis for the rational classification of dietary fiber and to guide the development of new healthy foods and the deep processing of food and its application.